The Patient Protection and Affordable Care Act’s Early Impact on Disparities in Access to Mental Health Treatment. - Hendel, Keren A. (Tufts Archival Research Center, 2017)
Using data from the National Survey on Drug Use and Health 2008-2015, econometric techniques are used to evaluate the impact of the portions of the Patient Protection and Affordable Care Act (ACA) implemented in 2014 on access to traditional and alternative mental health treatment for various socie-demographic groups. It is found that the ACA leads to higher rates of traditional treatment overall, no change in likelihood of receiving alternative treatment, and limited practically significant reduction in disparities in accessing traditional treatment (mainly for the unemployed and elderly).